Identifying the Gaps: An Assessment of Nurses' Training, Competency, and Practice in HIV Care and Treatment in Kenya. (May 2016) - Smith, Janel; Odera, Doris N.; Chege, Duncan; Muigai, Esther N.; Patnaik, Padmaja; Michaels‐Strasser, Susan; Howard, Andrea A.; Yu‐Shears, Janette; Dohrn, Jennifer
Abstract : N/A: Given the burden of HIV and the critical shortage of health workers in Kenya, in 2011 the National AIDS and STI Control Program recommended shifting HIV care and treatment tasks to nurses in settings without physicians and clinical officers in order to decentralize and scale‐up HIV services. In September 2013, ICAP at Columbia University conducted a survey with nurses in four health facilities in eastern Kenya to assess preparedness for task shifting. Findings indicated gaps in nurses' training, perceived competency, and practice in HIV care and treatment. Further investment in nurse capacity building is needed to bridge the gaps and prepare more nurses to provide high‐quality, comprehensive HIV care and treatment services to curb the epidemic in Kenya.